2008
DOI: 10.1002/ijc.23731
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Fas level and cancer mortality: Findings from a nested case–control study within a large‐scale prospective study

Abstract: Soluble Fas (sFas) is known to play an important role in the development of cancers of various sites. To confirm whether or not the serum sFas level can be a predictor of cancer, we conducted a nested case-control study within a large-scale population-based cohort study in Japan. Serum samples were collected from 39,242 participants (13,839 men and 25,403 women) at baseline, all of whom were followed until 1997 for mortality and until 1994 for cancer incidence. Three controls were randomly selected and matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Further studies with larger sample size are required to establish a precise cut-off point for that purpose. Tamakoshi A et al performed a nested case-control study within a large-scale prospective study and suggested that serum sFas has a possibility to detect people at high risk for cancer (regardless of cancer type) prior to diagnosis[15]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies with larger sample size are required to establish a precise cut-off point for that purpose. Tamakoshi A et al performed a nested case-control study within a large-scale prospective study and suggested that serum sFas has a possibility to detect people at high risk for cancer (regardless of cancer type) prior to diagnosis[15]. …”
Section: Discussionmentioning
confidence: 99%
“…Fas/FasL system has been investigated in a large variety of neoplasms[12-15]. However, few studies have been reported about gastric cancer to date.…”
Section: Introductionmentioning
confidence: 99%
“…Both in vitro and in vivo studies demonstrated that blocking of the Fas/FasL interaction with an FasL-neutralizing antibody inhibited Dox-induced toxicity in cardiomyocytes (Nakamura et al, 2000;Wu et al, 2002). In a recent study, an elevated level of sFas has been found in patients with several different cancers (Tamakoshi et al, 2008), and studies have shown that patients with increased levels of sFas during chemotherapy had a better overall survival (Perik et al, 2006;Pichon et al, 2006). The recent reports from others and our laboratory demonstrate that expression of sFas leads to improvement in cardiac function and overall survival in mice with ischemic myocardial injury Niu et al, 2006).…”
mentioning
confidence: 99%
“…It is also known that soluble agonistic and decoy receptor proteins concerning human Fas receptor system are useful biomarkers in serum, urine and other body fluids for early diagnosis [38], prognosis [39,40], response to drug treatment [41] and mortality [42] of many serious human diseases represented by cancers. The mutant hFasLECD containing the reactive cysteine residue conjugable to maleimide group containing compounds should also become a powerful molecular agent in developing devices for quantifying such disease specific biomarkers.…”
Section: Discussionmentioning
confidence: 99%